2009
DOI: 10.3354/meps08063
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid biomarkers in coldwater eelgrass meadows: elevated terrestrial input to the food web of age-0 Atlantic cod Gadus morhua

Abstract: Lipid classes, fatty acids (FAs), and stable carbon isotopes of FAs were used to investigate dietary sources of organic carbon for juvenile Atlantic cod Gadus morhua during settlement into eelgrass Zostera marina. Primary producers, epibenthic prey, zooplankton, and fish were collected from August to November 2002 in shallow (<10 m) eelgrass in Bonavista Bay, Newfoundland, Canada. Lipid data indicated that zooplankton (> 80 µm) were associated with fresh organic material, while seston (5-80 µm) had high levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 72 publications
1
19
1
Order By: Relevance
“…When all sources were considered together (uncorrected data by SIAR output contribution) to compute the trophic retention factor, the regression for essential FAs showed that there is a mechanism for ''trophic magnification,'' not just for 22:6v3 as proposed for cold seas (Parrish et al 2009), but for 20:4v6 and 20:5v3 within the coral reef food web. In the Gulf of Mexico coral reef food web, the EPA and DHA ratio is close to one in phytoplankton, the principal source of DHA (Table 3); however, TRF of DHA was 3.5 compared with EPA with TRF of 1.5, confirming that there is a preferential trophic accumulation for DHA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When all sources were considered together (uncorrected data by SIAR output contribution) to compute the trophic retention factor, the regression for essential FAs showed that there is a mechanism for ''trophic magnification,'' not just for 22:6v3 as proposed for cold seas (Parrish et al 2009), but for 20:4v6 and 20:5v3 within the coral reef food web. In the Gulf of Mexico coral reef food web, the EPA and DHA ratio is close to one in phytoplankton, the principal source of DHA (Table 3); however, TRF of DHA was 3.5 compared with EPA with TRF of 1.5, confirming that there is a preferential trophic accumulation for DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Trophic retention factor-FA biomarker tracers may provide an additional advantage for studying food webs in that their signals may persist through multiple trophic transfers (Hall et al 2006;Copeman et al 2009). The most important long-chain (C 20 -C 22 ) HUFAs in fish are ARA, EPA, and DHA (Sargent et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free-ranging eiders would not normally consume such high levels of 18:2n-6, with that FA typically present in proportions <12% in most marine bivalve species (Table1) (Joseph, 1982), as well as aquatic insects (Goedkoop et al, 2000;Sushchik et al, 2003) and plants (e.g. Copeman et al, 2009). Known diet items for free-ranging eiders would also be expected to have low lipid contents, so that 18:2n-6 would make very little contribution to total FA consumed.…”
Section: Diet To Adipose Isotopic Discrimination Factorsmentioning
confidence: 99%
“…This multivariate technique handles a large amount of variables simultaneously, and has been used by organic geochemists to determine organic matter sources and degradation of suspended and sinking particles in the oceans [110,111]. We have used PCA to determine marine, terrestrial, and anthropogenic organic inputs, and trophic relationships (e.g., [100,102,104,[112][113][114]). Fatty acid PCA continues to have a strong following [115][116][117], but more sophisticated multivariate statistical analyses are emerging too (see below).…”
Section: Multivariate Data Analysismentioning
confidence: 99%